Working Age Population and CO2 Emissions in Indonesia: : Household Approach - Mirta Dwi Wulandari (Politeknik Statistika STIS, 2021)
An increase in the working age population causes an increase in consumption which in turn will have an impact on increasing CO? emissions. The household is an element that must be responsible for increasing emissions of greenhouse gases because of their fossil fuels consumption. This study aims to observe the relationship of the working age population and the CO? emissions in households. This study use data from National Socio-Economic Survey (Susenas) 2019 with households consuming gasoline / diesel / kerosene for transportation, and LPG / kerosene for cooking as a unit of analysis. Apart from working age population as the main independent variable, socioeconomic characteristics (household size, income, residential area, poverty, age, sex, education, employment status, and access to modern fuels) are also used as control variables. Multiple regression analysis was used in this study. The results show that the working age population variable is positively correlated to total CO? emissions, transportation-related emissions, and cooking fuels emissions. Respectively, households dominated by members of working age (15-64 years) emitted 8.7%, 12.7%, 3.2% higher than households dominated by non working age (0-14 years and/or 65+ years). Providing sustainable transport system can be the best solution to reduce CO? emissions.